Moral Solidarity in Orphan Almsgiving: Reception and Institutionalization of Living Hadith in Sendang Agung Village - Nur Huda; Mohammad Rosyid; Masudi (Jurnal Living Hadis, 2026)
While orphan almsgiving is articulated in the hadith as a matter of individual religious conduct, it is reappropriated by the community of Sendang Agung Village as a collective and organized social action. This transformation, however, has received insufficient attention, particularly regarding the mechanisms of reception, institutionalization, and gift relations underlying it. This article examines the phenomenon as a manifestation of Living Hadith constitutive of moral solidarity within rural Muslim communities, with particular attention to the reception, institutionalization, and expression of gift relations embedded in the tradition. The study, methodologically, adopts a qualitative field research design, employing participant observation, in-depth interviews with religious leaders, mosque administrators, donors, committee members, and orphan beneficiaries, and documentary analysis of relevant hadith literature, with the Living Hadith framework and Berger and Luckmann’s theory of social construction and Mauss’s theory of gift-giving as the principal analytical lenses. The findings demonstrate that orphan almsgiving constitutes not merely an act of transient philanthropy but a locally institutionalized form of hadith reception. Through the successive processes of externalization, objectivation, and internalization, the prophetic value of concern for orphans is rendered into an enduring annual social practice. Through the theory of gift-giving, this practice engenders symbolic reciprocity, safeguards the dignity of orphan recipients, and reinforces the moral identity of the village community.